2009
DOI: 10.1051/0004-6361/200913326
|View full text |Cite
|
Sign up to set email alerts
|

Companion stars of type Ia supernovae and hypervelocity stars

Abstract: Context. Recent investigations of the white dwarf (WD) + He star channel of Type Ia supernovae (SNe Ia) imply that this channel can produce SNe Ia with short delay times. The companion stars in this channel would survive and potentially be identifiable. Aims. In this Letter, we study the properties of the companion stars of this channel at the moment of SN explosion, which can be verified by future observations. Methods. According to SN Ia production regions of the WD + He star channel and three formation chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 52 publications
7
90
1
Order By: Relevance
“…Identification of these remnant objects would help to support this scenario. The surviving companions from the model might also explain hypervelocity helium-rich stars like US 708 (e.g., Hirsch et al 2005) because of the short orbital periods at the moment of SN explosion (see also Justham et al 2009;Wang & Han 2009) 4 . Geier et al (2013) suggested that the CO WD + sdB system CD−30 11223 and the hypervelocity star US 708 might represent two different stages of an evolutionary sequence linked by an SN Ia explosion (the orbital velocity of the sdB at the moment of SN explosion will be about 600 km s −1 and thus close to the Galactic escape velocity).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these remnant objects would help to support this scenario. The surviving companions from the model might also explain hypervelocity helium-rich stars like US 708 (e.g., Hirsch et al 2005) because of the short orbital periods at the moment of SN explosion (see also Justham et al 2009;Wang & Han 2009) 4 . Geier et al (2013) suggested that the CO WD + sdB system CD−30 11223 and the hypervelocity star US 708 might represent two different stages of an evolutionary sequence linked by an SN Ia explosion (the orbital velocity of the sdB at the moment of SN explosion will be about 600 km s −1 and thus close to the Galactic escape velocity).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang & Han (2009) and Justham et al (2009) have suggested a single degenerate SN Ia scenario to explain the formation of the helium sdO US 708. Accordingly, a white dwarf accretes matter from a helium star in a close binary system.…”
Section: Discussionmentioning
confidence: 99%
“…The WD + He stars channel can explain SNe Ia with short delay times ( < ∼ 10 8 yr) (Wang et al 2009a,b;Meng & Yang 2010b), therefore this channel may be related to the young SSSs. In addition, the WD + He star channel may be responsible for the origin of the hypervelocity stars (Wang & Han 2009). The system HD 49798/RXJ 0648.0-418 is confirmation of the existence of a rapidly rotating massive WD + He star system.…”
Section: Discussion and Summarymentioning
confidence: 99%